Testicular choriocarcinoma with pelvic and pulmonary metastases: a case report - Bai, Xin; Liu, Xiao H.; Liang, Hai W.; Li, Yi S.; Shan, Biao F.; Tang, Jian M. (Frontiers in Oncology, 2024)
Testicular tumors represent a common form of solid tumor in young men, with choriocarcinoma of the testis being a rare, non-granulomatous germ cell tumor. It accounts for less than 0.3% of all testicular germ cell tumors. Pelvic and pulmonary metastases originating from testicular choriocarcinoma are exceptionally uncommon in men. This study describes a case of a 27-year-old male diagnosed with testicular choriocarcinoma, presenting initially with nausea, vomiting, and abdominal pain.Furthermore, this review encompasses cases of testicular choriocarcinoma in individuals aged 30 years and below, both in China and internationally, over the past 20 years.